THE USE OF WHISPERING GAME IN TEACHING LISTENING SKILL FOR YOUNG LEARNERS - Husni, Na'imatul; Cahyatie, Puja (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2024)
The research results show that the use of whispering games can improve the English listening skills of fifth grade students at SDN 5 Palembang.Listening skill possessed by each student were different because it was determined by the habit of practicing the listening skill that they do. It means the listening skill was found by how often someone to practice as a recipient of a message and pass that message to others. In whispering game, the students must really pay attention to the message that convey by their friends, which was consisted of some words. Therefore, the students mut focus to word by word that convey by their friends. Which one was conjunction, noun, or verb. Most of the students said that they listen clearer when it was whispered than spoken in loud voice. Because when in whisper, the students will concentrate and focus to what their friends said. Whispering game also can sharp the students’ listening skill because when in a whisper, they will pay attention to the accuracy of the message that convey by their friends. While the researcher asked about how many words that they listened clearly, most students stated that the words are so clear enough but they do not know how to write. It means that they should more careful to listen.